The Nordic welfare state in the 1990s: consequences of disinflation and fiscal consolidation in the three Nordic EU countries - Jaakko Kiander (Free University Berlin, Jean Monnet Centre of Excellence, 2003)
This paper reviews the current state of the so called Nordic welfare state, and the experiences of Denmark, Finland and Sweden in the 1990s in adjusting their public sectors to fiscal consolidation. The economic crises and structural changes of the 1990s are viewed as a part of adjustment to integration and globalisation, especially to financial deregulation. Even after these hardships the Nordic model remains clearly distinctive and in many respects successful. Although the Nordic welfare model has survived many difficulties, there lie further challenges in the future.The most important of them are possible tax competition which may threaten the financial basis of current welfare systems, especially in Denmark and Sweden, and expected demographic change, which will add excess burden to the public finances within the next 20 years. However the all Nordic countries have currently healthy fiscal surpluses, which gives them a better position than for most other Western European countries.
Keywords: 330; welfare state; integration; Nordic countries